PENGARUH SUHU AIR TERHADAP PROSES PEMBUATAN KOPI KINTAMANI BALI DENGAN METODE MANUAL BREW MENGGUNAKAN FRENCH PRESS TOOL - Achmadi, Rudhi; Nasyir Iskandar, Muhamad; Widiarto, Setyo (STABN Raden Wijaya Wonogiri, 2024)
Bali Kintamani coffee is one of the most authentic and exotic coffees grown in Indonesia. Kintamani Bali coffee has the character of citric acid (orange), and sweet brown sugar, where the taste is strongly influenced by the brewing method and brewing technique. This study aims to determine the results of steeping Bali Kintamani coffee with the manual brew method using a French press. The study used organoleptic tests to define the difference in results that occurred using different water temperatures from the ideal temperature. This study took as many as 20 experienced barista respondents because they were considered able to define the taste of brewing coffee to be served. This study found that steeping results using water temperatures above the ideal tend to have a more complex taste, but steeping results using temperatures below the ideal have a good level of taste balance without any dominating indicators. Keywords: Manual Brew, French Press, Water Temperature, Bali Kintamani, Organoleptic Test